Primary Immunodeficiency Disease Mimicking Pediatric Bechet's Disease - Mayuka Shiraki; Saori Kadowaki; Tomonori Kadowaki; Norio Kawamoto; Hidenori Ohnishi (MDPI AG, 2021)
Behcet's disease (BD) is a chronic inflammatory disease with multisystemic involvement. Its etiology is considered to involve complex environmental and genetic factors. Several susceptibility genes for BD, such as human leukocyte antigen (HLA)-A26, IL23R-IL12RB2, IL10 and ERAP1, in addition to the well-studied HLA-B51, were mainly identified by genome-wide association studies. A heterozygous mutation in TNFAIP3, which leads to A20 haploinsufficiency, was found to cause an early-onset autoinflammatory disease resembling BD in 2016. Several monogenic diseases associated with primary immunodeficiency disease and trisomy 8 have recently been reported to display BD-like phenotypes. Among the genes causing these diseases, TNFAIP3, NEMO, RELA, NFKB1 and TNFRSF1A are involved in the NF-κB (nuclear factor κ light-chain enhancer of activated B cells) signaling pathway, indicating that this pathway plays an important role in the pathogenesis of BD. Because appropriate treatment may vary depending on the disease, analyzing the genetic background of patients with such diseases is expected to help elucidate the etiology of pediatric BD and assist with its treatment. Here, we summarize recently emerging knowledge about genetic predisposition to BD.